1991
DOI: 10.1159/000181897
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inhibin as an Index of Ovarian Function in Women Undergoing Pituitary Suppression and Ovarian Stimulation in an in vitro Fertilization Program

Abstract: Serum inhibin concentrations, determined by radioimmunoassay, were measured in women undergoing pituitary suppression with buserelin and subsequently ovarian stimulation with human menopausal gonadotropin (hMG). Three types of treatment cycle were investigated, namely (1) cycles showing a normal ovarian response and resulting in a pregnancy; (2) cycles showing a poor response to the hMG, and (3) cycles previously showing a poor ovarian response but augmented with biosynthetic human growth hormone. Good correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…The rise in inhibin during gonadotrophin stimulation corresponds to earlier observations during cycles stimulated with clomiphene citrate-hMG (McLachlan et al, 1986;Hughes et al, 1990) without GnRH analogue pretreatment, and during GnRH analogue/hMG cycles (Matson et al, 1991) and adds weight to the suggestion that such assays might usefully indicate the level of follicular recruitment and maturation during controlled ovarian hyperstimulation cycles. Consistent with previous evidence reporting a significant correlation between immunoreactive inhibin and the number of follicles (McLachlan et al, 1986;Tsuchiya et al, 1989), there is significant correlation between the number of follicles and circulating levels of inhibin A and pro C in this study suggesting that these hormone measurements can be used as markers for follicular development in IVF.…”
Section: Discussionsupporting
confidence: 75%
“…The rise in inhibin during gonadotrophin stimulation corresponds to earlier observations during cycles stimulated with clomiphene citrate-hMG (McLachlan et al, 1986;Hughes et al, 1990) without GnRH analogue pretreatment, and during GnRH analogue/hMG cycles (Matson et al, 1991) and adds weight to the suggestion that such assays might usefully indicate the level of follicular recruitment and maturation during controlled ovarian hyperstimulation cycles. Consistent with previous evidence reporting a significant correlation between immunoreactive inhibin and the number of follicles (McLachlan et al, 1986;Tsuchiya et al, 1989), there is significant correlation between the number of follicles and circulating levels of inhibin A and pro C in this study suggesting that these hormone measurements can be used as markers for follicular development in IVF.…”
Section: Discussionsupporting
confidence: 75%
“…Serum E2 rises markedly and correlates strongly with total follicle number; no such correlation was seen for immunoreactive inhibin. Previous studies have indicated that El and immunoreactive inhibin appear to be equally good indicators of granulosa cell function (McLachlan et al, 1986, Buckler et al, 1988Matson et al, 1992). Our study contrasts with this; however, in these other studies not all the patients had PCOS and where they did there was no occurrence of multiple follicular development and only large follicles developed.…”
Section: Discussioncontrasting
confidence: 94%
“…Our study contrasts with this; however, in these other studies not all the patients had PCOS and where they did there was no occurrence of multiple follicular development and only large follicles developed. Matson et al (1992) selected patients in whom the follicles were greater than 14 mm in diameter, but even so found that immunoreactive inhibin concentration may be a more reliable indicator than El of the number of growing follicles as the correlation coefficient for immunoreactive inhibin and number of follicles ( R =0.71) was higher than that between E2 and follicle number (R = 0.5) on the day of the ovulatory trigger. It therefore appears that the relationship previously seen between immunoreactive inhibin and follicle number was not found in our study because of the high incidence of multiple follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactive inhibin (i-Inh) was assayed using reagents and conditions described previously and restandardized by Matson et al (1991) against a pool of serum obtained from women after treatment with hMG for in-vitro fertilization. One unit is equivalent to 1 p1 of the standard serum preparation and to 0.4 units of the WHO standard 86/690 (National Institute for Biological Standards and Control, South Mimms, UK).…”
Section: Lmmunoassaysmentioning
confidence: 99%